Rise from Challenges: Adversity Quotient and Career Adaptability - Kezia Ayu Teena; Anna Armeini Rangkuti; Herdiyan Maulana; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
The Industry 4.0 era, characterized by rapid technological advancements and dynamic challenges within the professional landscape, necessitates that all individuals develop their skills to avoid being replaced by technology and to effectively adapt to new job roles. Within this phenomenon, this research aims to explore the role and implications, analyzing research gaps related to adversity quotient and career adaptability by reviewing previous studies using a narrative literature review method. This study employs a narrative literature review approach, with a search conducted from 2010 to 2025, utilizing sources such as Google Scholar and Scopus. The findings overwhelmingly indicate a relationship and influence of adversity quotient on career adaptability. Additionally, several past studies have also utilized adversity quotient as a relevant variable in the context of careers and professions.